THE EFFECT OF FOOD PRICE VOLATILITY (FPV) ON INFLATION IN PAREPARE CITY - Tenriawaru, Andi Nixia; Amir, Ayu Anisa; Syam, Siti Hardiyanti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Food price volatility often occurs and cannot be avoided, including food price volatility that occurs in Parepare City. The effect of movement or changes in food prices appears to influence inflation, which in turn becomes the purpose of this study, namely to analyze the effect of changes in food prices on inflation in Parepare City. The analysis method used is multiple linear regression analysis. The data used is secondary data in the form of monthly time series from July 2018 to June 2021. The independent variables in this study are the food prices of rice, chicken meat, red chili, chicken eggs and granulated sugar. The results showed that the food prices of rice and chicken eggs have an increasing trend while the prices of chicken meat, red chili, and granulated sugar tend to decrease. The coefficient of determination test results shows that changes in food prices simultaneously positively and significantly affect inflation. The t-statistical test shows that partially changes in food prices of rice and chicken meat have a positive and significant effect on inflation while changes in food prices of red chili, chicken eggs and granulated sugar have a positive but insignificant effect on inflation. This research has implications for public policy to develop food prices stabilization policies, such as food reserve policies, market regulations, incentives for food producers, or social assistance programs to alleviate the impact of food inflation.